PENERAPAN MODEL PEMBELAJARAN INKUIRI MATA PELAJARAN BAHASA INDONESIA MATERI MENULIS TEKS EKSPLANASI PADA PESERTA DIDIK - Y, Yulisma (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2022)
The purpose of this study was to improve learning outcomes of explanatory text writing skills for students in class XI IIS I MAN 2 Bungo using an inquiry approach. Through an inquiry approach, the improvement of explanatory text-writing skills can be seen in both process and product. This research is a Classroom Action Research (CAR). The subjects of this study were students of class XI IIS I MAN 2 Bungo, totaling 20 students. The object of this research is the skill of writing explanatory text. This classroom action research was carried out in two cycles. Each cycle has four stages, namely: planning, implementation, observation, and reflection. Data was obtained from observations, interviews, tests, field notes, and documentation. Data analysis techniques were carried out qualitatively and quantitatively. The students' explanatory text writing skills are seen from the minimum completion criteria (KKM) achievement limit, which is 72 and becomes a consideration for the implementation of the next cycle. The results showed that the application of the inquiry approach could improve the learning outcomes of explanatory writing skills in class XI IIS I MAN 2 Bungo students, both process and product. The improvement of the process is shown from the attitudes of students, student activities, and learning atmosphere, namely students actively participate in learning to write explanatory texts, students dare to express opinions during discussions, students can work well together in groups, and students can follow and understand the steps of the inquiry approach well. Product improvement can be seen in the work of students. In the first cycle, the total score was 142.8 with an average value of 7.14 students with a complete description of 14 students (70%). Furthermore, in the second cycle, the total score is 161.3 with the average number of students increasing to 8,065 with complete student information as many as 17 students or 85%.